My first three days as a first-year – The autoethnography of an autistic student - Gouws, E.; Wassermann, J. (South African Journal of Higher Education, 2024)
My enrolment at university was a significant milestone in my life. During my first three days as a student with autism spectrum disorder, I experienced both positive and negative situations at different campuses, including overcrowded lecture halls, residences, faculty houses, and interacting with other students. My literature review and theoretical interpretation are guided by historical institutionalism and Bakhtin’s concept of “outsideness”. These frameworks address how historical events shape the social, political, and economic behaviour of institutions in a system that treats new students who must adapt to the university’s rules, regulations, and traditions as outsiders. The frameworks mentioned above were used to understand what I experienced during my first three days at university, which set the tone for the rest of my undergraduate education, punctuated by ableness, whiteness, masculinity, and fluctuating forms of support.